PERAN TEKNOLOGI TELEHEALTH DALAM PENINGKATAN EFEKTIVITAS LAYANAN HOME CARE: LITERATURE REVIEW - Dara Putri Handayani; Lilis Lismayanti (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The rapid advancement of information and communication technology has significantly transformed nursing services, particularly within homecare settings. Evidence across multiple studies indicates that telehealth and telenursing effectively overcome geographical barriers, improve the efficiency of care delivery, and expand accessibility to health services for diverse populations. The implementation of telehealth in homecare enables virtual interaction between nurses and patients through digital platforms such as video conferencing, mobile phones, short message services, and online applications, allowing continuous nursing care without requiring direct visits to healthcare facilities. Research further highlights that improved service quality in homecare is strongly associated with higher levels of patient satisfaction and trust, emphasizing the role of communication and service continuity in shaping user experience. Additionally, nursing telehealth has been shown to enhance the effectiveness of nursing care, shorten service distance and duration, and optimize nurses’ professional performance in providing comprehensive care. For patients with chronic illnesses, telehealth contributes to improved reassurance through remote monitoring, although some findings report no statistically significant differences in quality of life compared to conventional homecare services. In pediatric nursing, the integration of telenursing within application-based home care has been identified as a promising solution to increase healthcare accessibility, support developmental monitoring, strengthen parental education, and improve children’s health outcomes through flexible remote nursing support. Overall, the reviewed literature demonstrates that telehealth has a strong potential to improve homecare service quality and nursing care performance. However, challenges remain, including limitations in internet infrastructure, legal and financial frameworks, and the readiness of nursing human resources. Strengthened intersectoral collaboration and supportive policy development are required to optimize the future implementation of telehealth as an integral component of homecare services in Indonesia